Pengaruh pendidikan kesehatan dengan media video 1000 hari pertama kehidupan (HPK) terhadap tingkat pengetahuan dan motivasi ibu hamil dalam upaya pencegahan stunting - Prantara, Wulan; Virgian, Kharisma; Miskiyah, Miskiyah; Anggraeni, Surti (Holistik Jurnal Kesehatan, 2025)
Background: Nutritional status is one of the determining factors in building superior human beings in the future of Indonesia. One of the government's strategies in efforts to overcome stunting is to monitor and evaluate efforts to accelerate stunting prevention at the national, district or city level. Purpose: To determine the effect of health education video media on the knowledge and motivation of pregnant women in efforts to prevent stunting. Method: Quasi-experimental using one group pretest-posttest design. This study was conducted in May 2024 on 35 pregnant women who attended pregnancy classes in the Tanjung Health Center work area. Data analysis using the Wilcoxon Test. Results: participants had good knowledge at the time of the pretest, namely 16 people (58.1%), while at the time of the posttest all participants had good knowledge (100%). The value of ρ = ​​0.000 <0.05 with a confidence level of 95%, meaning that there is an influence of video media on the knowledge of pregnant women for the first 1000 days of life. At the time of the pretest, participants already had good motivation, namely 27 people (77.1%), while at the time of the posttest good motivation increased to 30 people (85.7%). The results of the Wilcoxon test obtained a value of ρ = ​​0.083> 0.05, which means that there is no influence of video media on the motivation of pregnant women for the first 1000 days of life. Conclusion: There is an influence of video media on changes in pregnant women's knowledge in preventing stunting. However, there is no influence between pregnant women's motivation and knowledge about stunting. Suggestion: This study is expected to be a reference for health workers in providing health promotion to increase mothers' knowledge and motivation regarding the first 1000 days of life and stunting by using effective media.   Keywords: First 1000 Days Life; Knowledge; Motivation; Stunting; Video Media.   Pendahuluan: Status gizi menjadi salah satu faktor penentu dalam menumbuhkan manusia unggul di masa depan Indonesia. Salah satu strategi pemerintah dalam upaya penanggulangan stunting adalah melakukan pemantauan dan evaluasi terhadap upaya percepatan penurunan stunting di tingkat nasional, kabupaten atau kota. Tujuan: Untuk mengetahui pengaruh pendidikan kesehatan media video terhadap pengetahuan dan motivasi ibu hamil dalam upaya pencegahan stunting. Metode: Quasi experiment menggunakan rancangan one group pretest-posttest. Penelitian ini dilaksanakan pada bulan Mei 2024 pada 35 ibu hamil yang mengikuti kelas ibu hamil di wilayah kerja Puskesmas Tanjung. Analisis data menggunakan Uji Wilcoxon. Hasil: partisipan memiliki pengetahuan baik pada saat pre test yaitu berjumlah 16 (58.1%), sedangkan pada post-test semua partisipan memiliki pengetahuan baik (100%). Perolehan ρ-value = 0.000 < 0.05 dengan tingkat kepercayaan 95%, berarti ada pengaruh media video terhadap pengetahuan ibu hamil tentang 1000 HPK. Pre-test partisipan sudah memiliki motivasi baik berjumlah 27 (77.1%), sedangkan pada saat post-test motivasi baik bertambah menjadi 30 (85.7%). Hasil uji Wilcoxon didapat ρ-value = 0.083 > 0.05 yang berarti tidak ada pengaruh media video terhadap motivasi ibu hamil tentang 1000 HPK. Simpulan: Ada pengaruh media video terhadap perubahan pengetahuan ibu hamil dalam pencegahan stunting. Namun, tidak ada pengaruh antara motivasi ibu hamil dengan pengetahuan stunting. Saran: Penelitian ini diharapkan dapat menjadi acuan bagi tenaga kesehatan dalam memberikan promosi kesehatan untuk meningkatkan pengetahuan dan motivasi ibu mengenai 1000 HPK dan stunting dengan menggunakan media yang efektif.   Kata Kunci: 1000 HPK; Media Video; Motivasi; Pengetahuan; Stunting.